Le sexuel dans le soin gériatrique. Une « difficulté dans la réalité » - Pascale Molinier (Genre, Sexualité et Société)
In this article, the author leans on her experience with psychodynamic analysis of work in a geriatric institution. She shows that the sexual, in the Freudian sense of the term, occupies a central place in geriatric care, constituting what Cora Diamond indicates as a "difficulty in the reality." This difficulty can, under certain organizational conditions, be assumed, elaborated and even sublimated in the care teams. But this dimension of the reality of bodies, fantasies and unconscious desire is evaded in most of conventional ethics. As a result, questions of sexual morality are posed within an inadequate theoretical frame. The vitality of the drive is denied for the benefit of a valuation of cognitive activities as the definitional characteristics of beinghuman . The ethic of the auxiliary nurses is the ethic of care. It turns out to be much more adapted to face this difficulty but exposes us to an awareness of our own vulnerability.